2006
DOI: 10.1111/j.1462-2920.2006.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial storage compound poly‐β‐hydroxybutyrate protects Artemia franciscana from pathogenic Vibrio campbellii

Abstract: SummaryInfections caused by antibiotic-resistant luminescent Vibrios can cause dramatic losses in aquaculture. In this study, the short-chain fatty acid b-hydroxybutyrate and its polymer poly-bhydroxybutyrate were investigated as possible new biocontrol agents. b-Hydroxybutyrate was shown to completely inhibit the growth of pathogenic Vibrio campbelli at 100 mM. Moreover, the addition of 100 mM of this fatty acid to the culture water of Artemia nauplii infected with the V. campbelli strain significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
126
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 45 publications
9
126
1
11
Order By: Relevance
“…Lee et al [27] evaluated cell adhesion of various aliphatic polyesters and they found that (RS)-PHB have low cell adhesion because of the surface accumulation of methyl groups. Defoirdt et al [28] reported that short-chain fatty acids like PHB showed a strong growth-inhibitory against pathogenic V. campbellii . Recently PHB was proven to be an immunostimulant in fish [29].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [27] evaluated cell adhesion of various aliphatic polyesters and they found that (RS)-PHB have low cell adhesion because of the surface accumulation of methyl groups. Defoirdt et al [28] reported that short-chain fatty acids like PHB showed a strong growth-inhibitory against pathogenic V. campbellii . Recently PHB was proven to be an immunostimulant in fish [29].…”
Section: Discussionmentioning
confidence: 99%
“…[37], [38], [39], [40], [41], [42]. Taken together, this suggests that a reduction of M. rhodesianum abundance allows colonization or over-growth by other bacteria, some of which are pathogenic.…”
Section: Discussionmentioning
confidence: 99%
“…PHB dapat mengaktifkan mekanisme pertahanan nonspesifik dengan cara melepaskan asam lemak yang dapat melindungi udang dari patogen. Asam lemak dapat menyediakan energi bagi udang dan menghambat pertumbuhan patogen (Defoirdt et al, 2007). Penggunaan PHB pada Artemia dapat meningkatkan sistem imun dengan menghambat pertumbuhan bakteri patogen (Nhan et al, 2010).…”
Section: Pendahuluanunclassified